Collaborative Governance In The Handling of Stunting Program In East Flores District - Fernandes, Dominikus; Daud Niga, Jacoba; Seran Klau, Rikhardus (Green Publisher Indonesia, 2022)
Stunting management and prevention programs generally use specific nutrition intervention approaches and sensitive nutrition interventions. Several studies have shown that interventions that are effective in reducing the prevalence of stunting are still limited, although a lot of data captures and reveals the sub-focuses on nutrition, food security and WASH (water, sanitation and hygiene), PMT, multi-sectoral approaches and health promotion programs but so far this has not been enough. obtain definite information regarding the prevention and treatment of stunting. On the other hand, studies related to capacity implementation, especially those carried out by several government agencies in an integrated manner, have not shown a reduction in the prevalence of stunting. Efforts to reduce the prevalence of stunting in the form of collaborative governance are very strategic considering that the synergy (government, private sector and the community) is needed when a specific nutrition intervention approach or a nutrition-sensitive intervention is carried out. Organizationally, currently efforts to prevent and treat stunting in East Flores Regency are marked by the formation of the Task Force: Convergence, Synergy, Collaboration to Accelerate Stunting Reduction which is a Task Force (collaborative governance) consisting of bureaucratic and non-bureaucratic elements. The entire observation includes all agencies that are members of the Stunting Handling Convergence Task Force. Interviews were conducted using a structured interview list with designated OPD leaders and staff; interview with street level implementation. Furthermore, observations were made at the Posyandu activity location. The collected data are then categorized and analyzed according to the research objectives. The results showed that the collaborative governance model for the prevention and treatment of stunting showed significant results, namely a decrease in the number of stunting by 2% (previously it was 22% to 20%); This fact is mainly supported by the optimal performance of the Stunting Convergence Task Force.